Role of biologics and biosimilars in inflammatory bowel disease: current trends and future perspectives - Rawla P (Dove Medical Press, 2018)
Prashanth Rawla,1 Tagore Sunkara,2 Jeffrey Pradeep Raj3 1Department of Internal Medicine, Memorial Hospital of Martinsville and Henry County, Martinsville, VA, 2Division of Gastroenterology and Hepatology, The Brooklyn Hospital Center, Clinical Affiliate of The Mount Sinai Hospital, New York, NY, USA; 3Department of Pharmacology, St John’s Medical College, Bangalore, India Abstract: Inflammatory bowel disease (IBD) is an idiopathic chronic inflammatory disease of the gastrointestinal system. The spectrum is of predominantly two types, namely, ulcerative colitis and Crohn’s disease. The incidence of IBD has been increasing steadily since 1990, and so the number of agents used in their treatment. Biologics that are derived partly or completely from living biological sources such as animals and humans have become widely available, which provide therapeutic benefits to the IBD patients. Currently, monoclonal antibodies against tumor necrosis factor-alpha (infliximab, adalimumab, certolizumab, and golimumab), integrins (vedolizumab and natalizumab), and interleukin (IL)-12 and IL-23 antagonists (ustekinumab) are approved for use in IBD. Biosimilars of infliximab and adalimumab are also available for the treatment of IBD. This review summarizes the clinical pharmacology, studies leading to their approval, overall indications and their use in IBD, usage in pregnancy and lactation, and the adverse effects of these agents. This review also summarizes the recent advances and future perspectives specific to biologics and biosimilars in IBD. Keywords: inflammatory bowel disease, Crohn’s disease, ulcerative colitis, biologics, biosimilars, tumor necrosis factor, integrin, interleukin, adalimumab, Humira®, certolizumab, Cimzia®, golimumab, Simponi®, infliximab, Remicade®, vedolizumab, Entyvio, natalizumab, Tysabri®, ustekinumab, Stelara®